Pulmonary alveolar microlithiasis: A case report - Kassab, Azhar K.; AL-Sakkal, Noel S.; Rashid, Sameeah A. (Zanco Journal of Medical Sciences (ZJMS), 2015)
Background and objectives: Pulmonary alveolar microlithiasis is rare disease characterized by the presence of numerous small calculi within the alveolar spaces.Case report: 39-year-old female with pulmonary alveolar microlithiasis is described, in which the diagnosis was suspected clinically and radiologically and confirmed histopathologically. The clinical, pathogenesis and pathology are briefly reviewed.